ALTERNATIF PEMIDANAAN TERHADAP PELAKU PENYALAHGUNAAN NARKOTIKA DALAM KEBIJAKAN KRIMINAL DI INDONESIA - Ratri Novita Erdianti (Faculty of Law, University of Muhammadiyah Malang, 2017)
Narcotics crime in Indonesia becomes a problem that until now never ceased. One of the problems is the increasing number of narcotics abusers. In our country, narcotic users/narcotics addicts can already be said as a criminal offender. In the Narcotics Act no. 35 of 2009 explained that what are meant by Narcotics Abusers are people who use Narcotics without rights or against the law. Persons who use narcotics unlawfully and unlawfully herein may be classified as addicts and distributors who use and conduct circulation. In the narcotics law, a drug addict victim of narcotics must undergo medical rehabilitation and social rehabilitation. But in reality, the article for narcotics abusers is more directed at other positions in the positions of dealers whose criminal consequences become imprisonment. This is for the author less appropriate. So that efforts made in solving cases of perpetrators of criminal acts become part of criminal policy in the context of the prevention of narcotics crime. The problem that the writer raised is about the relevance of criminal prison for narcotics abusers with the purpose of punishment and how the application of alternative punishment against narcotics abusers from the perspective of criminal policy. This study was conducted using normative juridical, which examines Law no. 35 of 2009 which regulates the form of punishment for the perpetrators of narcotics abuse is associated with the theories in criminal law